2010
DOI: 10.2135/cropsci2008.09.0529
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Root Characteristics of Peanut in Hydroponics and Pot Studies

Abstract: A large root system can be an important character for drought tolerance. Measuring root characteristics in soil medium is tedious, time consuming, and labor intensive. The objective of this study was to determine the association between root characteristics of peanut (Arachis hypogaea L.) grown in hydroponics and in pot experiments. Twelve peanut genotypes were planted in a randomized complete block design with four replications in a hydroponics study, a small pot, and a large pot experiment. The studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
3
13
0
1
Order By: Relevance
“…These results agree with previous findings on groundnut (Teerayoot et al 2010;Ntare and Williams 1998). These results indicate that screening for drought tolerance in groundnut is specific to the drought conditions that are imposed, which agree with recent results in a wide array of germplasm from the reference collection of groundnut (Hamidou et al under review).…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with previous findings on groundnut (Teerayoot et al 2010;Ntare and Williams 1998). These results indicate that screening for drought tolerance in groundnut is specific to the drought conditions that are imposed, which agree with recent results in a wide array of germplasm from the reference collection of groundnut (Hamidou et al under review).…”
Section: Discussionsupporting
confidence: 93%
“…The difference of genotypes stem weight under water stress compared to well water conditions suggested that drought tolerance may be adaptive since its important role in accumulation of assimilates storage for vegetative growth and grain filling. These results agree with findings on groundnut reported by several authors [15,16,17].…”
Section: Resultssupporting
confidence: 94%
“…Resultados similares foram ralatados por Mian et al (1993), em que o crescimento radicular vigoroso resultou em crescimento vigoroso da parte aérea do trigo, por Girdthai et al (2010), em amendoim, e por Kennedy & Hutchinson (1999), em algodão. Isso leva a crer que a cultura tende a manter equilíbrio na sua relação raiz/parte aérea; a ocorrência de prejuízos em um dos fatores será acompanhada de redução do outro fator.…”
Section: Resultsunclassified